EFEKTIVITAS PROGRAM SENSUS PENDUDUK KABUPATEN PROBOLINGGO SECARA ONLINE DI MASA PANDEMI COVID-19 TAHUN 2020 - Agis, Mariatul Khiptia; Septiandika, Verto (Universitas Panca Marga, 2021)
Population data collection is an activity carried out by orders to determine the population of the Republic of Indonesia. The Central Statistics Agency made a policy related to population data collection during the Covid-19 period, namely the 2020 population census (SP2020) which began to be carried out in February-March 2020, filling out the online population census can be accessed through the Central Statistics Agency website census.bps.go.id. The online population census is the first time data collection has been conducted online in the State of Indonesia. The results of this study are related to the population census in Probolinggo Regency which is running effectively, the online population census is a challenge in itself for census officers, because many people who live in rural areas still lack technology because of the difficulty of accessing signals in the village. The census also needs to carry out data collection manually by visiting the houses of people who have not filled in their data online, while still adhering to health protocols. In this study the authors used descriptive qualitative methods.